Preparation of a Questionnaire for Clean and Healthy Behavior and Multivitamins to Measure Knowledge, Attitudes and Behavior as Prevention Efforts During the COVID-19 Pandemic - Sisilia Christina Ari Widiastuti; Yosef Wijoyo; Nunung Priyatni (Sanata Dharma University, 2022)
Clean and Healthy Behavior (PHBS) is a movement that aims to improve the quality of the life and health of a person and society. One way to prevent the spread of COVID-19 is to live a clean and healthy lifestyle and increasing a person’s endurance can be done by taking multivitamins. This study aims to develop a PHBS and Multivitamins questionnaire that can be used to evaluate the knowledge, attitudes and behavior of Pelita Bangsa Health Vocational School students. This quantitative research was conducted in two stages. The first stage aimed to develop the PHBS and Multivitamin questionnaire’s framework, and the second stage was to test the validity and reliability. The questionnaire was made in three parts, including knowledge, attitude and behavior. The knowledge parts used the Guttman scale, while the attitude and behavior parts used a Likert scale. Questionnaire statements were considered valid by experts’ judgment. From the results of the validity and reliability tests of the questionnaire using Cronbach's alpha analysis, the results of the questionnaire were declared valid and reliable with a value above 0.60. The resulting questionnaire consists of 25 statements of knowledge, 20 statements of attitude and 20 statements of behavior. This research instrument can be used to measure students’ knowledge, attitudes and behavior in Pelita Bangsa Health Vocational School.